A synergistic interactions of Algerian essential oils of Laurus nobilis L., Lavandula stoechas L. and Mentha pulegium L. on anticholinesterase and antioxidant activities - Yakoubi, Rima; Megateli, Smain; Sadok, Tahar Hadj; Bensouici, Chawki; Bagci, Eyup (Elsevier, 2021)
This study aims at performing a chemical analysis of the essential oils of Laurus nobilis (LNEO), Lavandula stoechas (LSEO) and Mentha pulegium (MPEO) by GC-MS. The possible synergistic effects of their combinations on anticholinesterase and antioxidant activities were investigated. LNEO was dominated by 1,8-Cineole. Pulegone was found to be the major constituent of MPEO, while fenchone was the major component present, along with camphor in LSEO. LSEO was found to have the highest AChE inhibitor (17.73 +/- 2.23 mu g/mL) that matched the capacity of galantamine and the highest BChE inhibitor (1.61 +/- 0.34 mu g/mL) which is more than galantamine. A total of 13 combinations were obtained by mixing the EOs in binary and ternary mixtures at different ratios. CompuSyn software was used to allow automated simulation of synergism and/or antagonism. Of these, LSEO in very strong synergy with MPEO at a 2:1 ratio displayed 0.08 combination index (CI) on BChE. Even, the combination of LNEO with LSEO at different ratios showed synergistic effect against both enzymes. A significant antioxidant activity was displayed by LNEO. Of interest, LNEO is considered to interact very strong synergistically with either LSEO or MPEO in a 2:1 ratio in CUPRAC. The same combinations exhibited strong synergistic action in DPPH and ABTS. Summing up, the present work highlights the importance of the synergistic interaction of EOs as promising and ideal alternatives to the food and pharmaceutical industries as it leads to diminishing their effective doses consequently improving the safety profile with lower side effects while increasing their efficiency.
Keywords: Essential oil; Anticholinesterase; Antioxidant; Synergy